Morphological evaluation of obstetric hysterectomy specimen in females with postpartum hemorrhage - Chaturvedi, Madhu; Shaikh, Niha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Obstetric hysterectomy (OH) is the removal of the uterus at the time of caesarean section, following vaginal delivery or within the puerperium period. Despite developments in the conservative medical &surgical management of OH, it remains a lifesaving technique for the management of persistent hemorrhage refractory to conservative control. Histopathological examination of the specimen is necessary as it determines the cause of OH and confirms the clinical and radiological indications. Methods: This was cross-sectional observational study conducted from January 2017 to December 2022. It was conducted on 62 obstetric hysterectomy specimens. Results: The proportion of OH was 6.05% out of a total 1024 hysterectomies. The age range of the study population was 20-45 years with a mean of 30.35±5.25 years. The trend towards OH increased with an increase in LSCS and it has been considered as an underlying high-risk factor for OH. The chief morphological abnormalities found were placenta accreta, placenta previa, placenta increta, placenta percreta, and retained placenta, followed by subinvolution. The radiological and morphological findings in 21 cases showed a statistically significant association. Conclusions: Abnormal placentation is the predominant cause of obstetric hysterectomy. The association between the rising CS rate and incidence of obstetric hysterectomy with a history of CS is attributable mostly to the occurrence of morbidly adherent placenta/placenta increta These abnormalities are amenable to early diagnosis by imaging methods.